Efficacy and Mechanism of Compound Danshen Dripping Pills on Disseminated Intravascular Coagulation Animal Model - Jing Wang; Yue Feng; Xin-Xin Li; Rui Yang; Peng-Yu Han; Xiao-Hui Ma; Qing-Hua Hu (World Journal of Traditional Chinese Medicine, 2025)
Objective: To investigate the effects of compound Danshen dripping pills (CDDP) on diffuse intravascular coagulation (DIC) and explore the possible mechanism of CDDP based on transcriptomic analysis. Materials and Methods: We replicated animal models of DIC using different inducers and observed the effects of CDDP on the survival rate of the model animals, hepatic and gastric fundus blood flow, abnormal prothrombin time (PT), fibrinogen (FIB) content and inflammatory factors, liver and kidney injury index. Thereafter, whole-blood transcriptome sequencing was performed, and the main target genes were selected for verification. Results: CDDP improved the survival rate of model animals, increased blood flow in the liver and stomach, improved PT and FIB values, inhibited the elevated serum levels of tumor necrosis factor-alpha and interleukin-10, increased the activity of glutamic pyruvic transaminase and glutamic oxaloacetic transaminase, and enhanced the levels of blood urea nitrogen and creatinine. Whole-blood transcriptome sequencing analysis showed that CDDP may regulate immune inflammatory response, oxidative stress, platelet activation and aggregation, and cell apoptosis in DIC. Quantitative polymerase chain reaction (qPCR) further confirmed that CDDP improved the abnormal expression of Sqstml, Ctsd, Mylk2, and Nfkbib in the model animals. Conclusions: CDDP exerts a protective effect on the primary organs of animal models of DIC by improving organ blood flow and coagulation abnormalities and inhibiting the expression of inflammatory factors. In addition, CDDP improved the prognosis of animal models of DIC by increasing the expression of key disease-related genes, such as Sqstml and Nfkbib.